Kepastian Hukum Kewenangan Pengelolaan Sektor Wisata Aceh Singkil Dalam Upaya Meningkatkan Pendapatan Asli Daerah (PAD) (Studi Dinas Pariwisata, Badan Pengelolaan Keuangan Kabupaten Aceh Singkil Dan BKSDAE) - Syifa Munawwarah (Iuris Studia: Jurnal Kajian Hukum, 2020)
Aceh Singkil is one of the districts that implements special autonomy in the administration of regional government based on Law Number 11 of 2006 concerning Aceh Governance. The specialty of Aceh is regulated in Article 3 of Law Number 44 of 1999 concerning the Implementation of Privileges for the Special Province of Aceh. Aceh Singkil has abundant natural resources in the tourism sector. Even so, there is a contradiction in the management of the Aceh Singkil tourism sector which is regulated in Law Number 10 of 2009 concerning Tourism, the Regency Regional Government which manages the tourism sector but according to Article 4 letter z Government Regulation Number 3 of 2015 concerning National Government Authority in Aceh is implemented by the Central Government through the Natural Resources and Ecosystem Conservation Agency. This study uses a normative juridical research method with a statute approach. Using primary data and secondary data. Data collection tools for interviews, observations, and literature study. The results show that the management authority of the Aceh Singkil tourism sector occurs dualism and does not provide legal certainty so it is necessary to rearrange statutory regulations by giving absolute authority to regional governments to process and manage their own government affairs in the tourism sector as this is supported by Article 30 of Law No. 10 of 2009 concerning Tourism. So that it can provide and increase good Regional Original Income can also be felt directly by Aceh Singkil.